The complexities in diagnosing intradiaphragmatic extrapulmonary sequestration: a case report - Anna-Kaelle K. J. Ramos; Tori R. Teramae; Collin G. Z. Liang; Miriam L. Brazer; Russell K. Woo (SpringerOpen, 2023)
Abstract Background Extralobar pulmonary sequestration-a congenital lung malformation characterized by nonfunctional lung tissue with its own visceral pleura and without a connection to the normal tracheobronchial tree-is often surgically resected given the potential for infectious complications. We report a case of a child with extralobar pulmonary sequestration in a rare and challenging intradiaphragmatic location, which made preoperative identification and planning difficult. Case presentation A 2-year-old boy presented for follow-up of a large left extralobar pulmonary sequestration initially diagnosed on an antenatal ultrasound. Follow-up imaging, including prenatal MRI and postnatal CT angiography, was inconclusive on the precise location of the extralobar pulmonary sequestration in relation to the diaphragm but did reveal a subdiaphragmatic arterial supply from a branch off the celiac trunk. Planned resection with diagnostic thoracoscopy revealed the mass to seemingly be below the diaphragm; however, subsequent abdominal laparoscopy identified it to be within the diaphragm. Once the supplying vessel off the celiac trunk was controlled and divided, the mass was circumferentially excised from the edges of the diaphragmatic muscle. The remaining diaphragmatic defect was then closed, and the patient did well postoperatively. Conclusions This case demonstrates the difficulty of making a definitive diagnosis of intradiaphragmatic extralobar pulmonary sequestration without operative intervention. CT angiography and identification of the sequestration's arterial supply may not be conclusive in determining the precise location if in close proximity to the diaphragm.